REACTS TO US ELECTION RESULT” VIDEO IN THE INDEPENDENT YOUTUBE CHANNEL - Fadhilah Tsaqila Akhyar; Juli Rachmadani Hasibuan (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
The study outlines hate speech on “Live: Trumps reacts to US election result” video in the Independent Youtube Channel. This study aimed to determine types and intentions of hate speech used in the Youtube comment. This study used descriptive qualitative and the research data were analyzed using Mondal (2017) theory to describe type of hate speech found on the comment section while Kreidler (2002) theory were used to showed the intentions of the data. By identifying the comments which are classified contain hate speech, using Mondal (2017) and Kreidler (2002) theory, this study showed that were four out of ten types of hate speech found, namely other, behavior, physical, and sexual orientation. While the highest intentions of the data occurred on mocking and the rests are accusing, insulting, insinuating, and blaming someone.REACTS TO US ELECTION RESULT” VIDEO IN THE INDEPENDENT YOUTUBE CHANNEL